2023
DOI: 10.1140/epjd/s10053-023-00630-8
|View full text |Cite
|
Sign up to set email alerts
|

Dusty plasma in active galactic nuclei

Abstract: For many years we have known that dust in the form of a dusty-molecular torus is responsible for the obscuration in active galactic nuclei (AGN) at large viewing angles and, thus, for the widely used phenomenological classification of AGN. Recently, we gained new observational and theoretical insights into the geometry of the torus region and the role of dust in the dynamics of emerging outflows and failed winds. We will briefly touch on all these aspects and provide a more detailed update of our dust-based mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 242 publications
0
2
0
Order By: Relevance
“…This can be interpreted to be predominantly the intrinsic color excess expected for the majority of type I QSOs (Richards et al 2003). This extinction originates in the circumnuclear medium, e.g., in an obscuring torus, a warped disk-like structure, or an outflowing clumpy wind within ∼1 pc from the supermassive black hole Gohil & Ballantyne 2017;Gaskell & Harrington 2018;Gaskell et al 2023), and the host galaxy interstellar medium, also see Stolc et al (2023) and Czerny et al (2023c) for discussions. Dust can also be present on the scales of a few thousand gravitational radii, i.e., on subparsec scales, within the BLR clouds (Pandey et al 2023).…”
Section: Relation To the Extinction Curve And E B − Vmentioning
confidence: 95%
“…This can be interpreted to be predominantly the intrinsic color excess expected for the majority of type I QSOs (Richards et al 2003). This extinction originates in the circumnuclear medium, e.g., in an obscuring torus, a warped disk-like structure, or an outflowing clumpy wind within ∼1 pc from the supermassive black hole Gohil & Ballantyne 2017;Gaskell & Harrington 2018;Gaskell et al 2023), and the host galaxy interstellar medium, also see Stolc et al (2023) and Czerny et al (2023c) for discussions. Dust can also be present on the scales of a few thousand gravitational radii, i.e., on subparsec scales, within the BLR clouds (Pandey et al 2023).…”
Section: Relation To the Extinction Curve And E B − Vmentioning
confidence: 95%
“…We are still far from fully understanding the physical processes of the plasma in the broad-line region (BLR), such as what the densities and temperatures are (Popović 2003;Marziani et al 2020), how to predict the observed emission line ratios (e.g., Ilić et al 2012;Netzer 2020), understand the production of diffuse BLR continuum emission (Chelouche et al 2019), the presence and role of dust (Baron et al 2016;Czerny et al 2023), or determine the location and origin of the Fe II emission (e.g., Baldwin et al 2004;Gaskell et al 2022). For sure, a promising approach for these investigations is to exploit large spectral data sets and provide catalogs of their spectral properties, as has been done for more than half a million of quasars from the Sloan Digital Sky Survey (SDSS; Rakshit et al 2020).…”
Section: Introductionmentioning
confidence: 99%